2022
DOI: 10.24289/ijsser.1164545
|View full text |Cite
|
Sign up to set email alerts
|

Educational behavior of the students in the design studios during the pandemic time

Abstract: The main aim of this paper is to demonstrate the process of adapting architecture students to the pandemic condition in the design studios due to wearing face masks and social distance measures. An architectural design studio is different from a normal classroom due to the open space for open discussion and dialogue and group work. The methodology of the research was designed based on the quantitative method with the application of the Likert scale questionnaire and analyzing the data in SPSS. The findings of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Despite both negative and positive literature on the influences of COVID-19 on education, the results of the research demonstrated that the students preferred to follow their style of activities in the design studio (Tafahomi, 2022a;Tafahomi, 2022b) as mentioned in terms of interaction through desk-crits by Schon (Schon, 1987). The studies mentioned the positive effects of the pandemic time on blended learning (Delialioglu & Yildirim, 2007;Gulbahar & Madran, 2009), however, the students' answers demonstrated that they preferred a physical class for social interaction.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Despite both negative and positive literature on the influences of COVID-19 on education, the results of the research demonstrated that the students preferred to follow their style of activities in the design studio (Tafahomi, 2022a;Tafahomi, 2022b) as mentioned in terms of interaction through desk-crits by Schon (Schon, 1987). The studies mentioned the positive effects of the pandemic time on blended learning (Delialioglu & Yildirim, 2007;Gulbahar & Madran, 2009), however, the students' answers demonstrated that they preferred a physical class for social interaction.…”
Section: Discussionmentioning
confidence: 95%
“…While the study criticized the unclear scales in the Likert questionnaire (Joshi et al, 2015), the Likert scale questionnaires were applied in educational research, importantly concerning the students' cases in the teaching and learning qualities (Li, 2013;Hartley, 2014;Huertas-Delgado et al, 2019;De Campos et al, 2020). Likert scale questionnaires were common due to the cluster of answers, the ability to sort data, and adaptation to statistical analysis (De Campos et al, 2020;Tafahomi, 2022a;Yang et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One-on-one desk critiques are customary practices preferred by students (Tafahomİ, 2022) in studio settings, wherein learners present ideas for a specific assignment and receive formative feedback from a studio master who responds, critiques, and guides the learners (Goldschmidt et al, 2010;Smith & Boyer, 2015). The asymmetrically power-structured master-apprentice pedagogical model remains ubiquitous as the core design disciplines (Achten, 2015;Ahmad et al, 2020;Brzezicki, 2020;Ceylan et Vol.16 Nr.5, 2023, Art.…”
Section: The Master-apprentice Model As the Dominant Design Pedagogy ...mentioning
confidence: 99%